Evaluation of community knowledge and attitude toward COVID-19: the case of Hawassa city, Sidama, Ethiopia - Warssamo, Birhanu Betela (Frontiers in Public Health, 2024)
Background: Scientific information on the knowledge and attitude at community level on COVID-19 pandemic is a vital step for effective controlling measures. This study was aimed to investigate the level of knowledge and attitude of Hawassa city residents toward COVID-19 and interaction among knowledge and attitude on COVID-19.A community based cross-sectional study with stratified random sampling was used from June 2020 to August 2020. Five hundred and eighty-seven residents were selected for the study which was aimed to evaluate their knowledge and attitude on COVID-19 using a standardized structured questionnaire. Data were collected using face-to-face interview with strictly follow WHO and the ministry of health Ethiopia guidelines for Covid-19 prevention. Attitude and knowledge were categorised based on the mean score value. Descriptive statistics and two independent multiple logistic regressions were applied to identify possible determinants of knowledge and attitude using SPSS version 20 set at 95% CI with p-value < 0.05 considered statistically significant.Results: 61.7% of the participants were knowledgeable about the virus and 65.9% had a positive attitude towards COVID-19. Educational level with categories second degree and above (AOR= 29.709, 95% CI= 1.239 -712.55), first degree (AOR= 3.476, 95% CI= 3.278 -22.02), certificate/diploma (AOR= 1.062-18.24, 95% CI= 1.062 -18.24 ), and grade 12 completed (AOR= 1.903, 95% CI=2.12 -6.809), employment status of respondents who were self-employed (AOR=9.545, 95% CI=1.165 -78.173), and employed respondents (AOR= 10.053, 95% CI= 1.783 -56.673), reading interest with categories always (AOR= 34.45,, sometimes (AOR= 17.24, 95% CI=17.213 -1661.966), habit of using social media with categories always (AOR=38.708, 95% CI= 5.086 -294.610), and sometimes (AOR= 3.432, were the significant explanatory variables that were correlated with knowledge of the respondents.Although the knowledge and attitude of respondents toward COVID-19 was positive, there is a need to use more effective strategies to improve knowledge and attitude toward COVID-19 and knowledge rising on preventive behaviours among the community was mandatory.to attain better results. Educational level, use of social media and reading habit of the respondents appears to play significant role in determining their level of knowledge and attitude toward COVID-19.